Effects of learning accessibility as a mediator between learning styles and blended learning in higher education institutions during the Covid-19 pandemic - Razali, Fazilah; Sulaiman, Tajularipin; Mohd Ayub, Ahmad Fauzi; Abdul Majid, Noraziela (UiTM Press, 2022)
Technology has been rapidly implemented in the learning process during the COVID-19 pandemic. It gives rise to new challenges, especially in higher learning institutions, in planning and mobilizing a sustainable learning environment. Initiatives have been taken to introduce different learning methods using the Learning Management System (LMS), that provide students with a more convenient and flexible way of learning. Thus, this study aims to determine the effects of learning accessibility as a mediator between learning styles and blended learning among students of higher education during the COVID-19 pandemic. A quantitative method using instruments from the Visual, Aural, Read and Kinaesthetic sensory (VARK) model has been selected. A total of 208 students from Universiti Putra Malaysia (UPM) have been randomly chosen as respondents who have fully utilized the LMS during the pandemic. Findings reveal that learning accessibility poses a partial mediation effect between learning styles and blended learning among students of higher education. This finding is significant and has achieved the Goodness-of-fit index (GFI). Therefore, it is proven that there are positive effects among students of higher learning institutions in Malaysia with a learning accessibility lean toward the LMS platform that increases blended learning and adaptability, prompted by the changes in the learning environment during the COVID-19 pandemic.